2016
DOI: 10.1007/s11010-016-2659-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic conditions increases H2S-induced ER stress in A2870 cells

Abstract: Hypoxia - a state of lower oxygen demand-is responsible for a higher aggressiveness of tumors and therefore a worse prognosis. During hypoxia, several metabolic pathways are re-organized, e.g., energetic metabolism, modulation of pH, and calcium transport. Calcium is an important second messenger that regulates variety of processes in the cell. Thus, aim of this work was to compare H2S modulation of the intracellular calcium transport systems in hypoxia and in cells grown in standard culture conditions. For al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Extensive increase or decrease in ER stress disrupts the balance of bone homeostasis and physiology [ 30 ]. BMSCs adapt themselves in a native hypoxic microenvironment in vivo [ 31 33 ], which always serves as an important stimulus of ER stress [ 34 ]. BMSCs had impaired chondrogenic potential after isolation and culture under normoxic conditions in vitro [ 35 , 36 ] , in accordance with the change in ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive increase or decrease in ER stress disrupts the balance of bone homeostasis and physiology [ 30 ]. BMSCs adapt themselves in a native hypoxic microenvironment in vivo [ 31 33 ], which always serves as an important stimulus of ER stress [ 34 ]. BMSCs had impaired chondrogenic potential after isolation and culture under normoxic conditions in vitro [ 35 , 36 ] , in accordance with the change in ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been shown to control the intensity of Ca 2+ signaling in cancer cells through IP3Rs (103). In addition, Lencesova et al (104) previously demonstrated that hydrogen sulfide causes ER stress and apoptosis under hypoxic conditions, suggesting that IP3Rs are closely associated with apoptosis in OC cells. Additionally, stable TAT-fused IP3R1-derived peptides can increase cisplatin-induced Ca 2+ flux from the ER into the cytosol and mitochondria, sensitizing OC cells to cisplatin by targeting the BH4 structural domain of Bcl-2 (Table II) (105,106).…”
Section: Intracellular Ca 2+ Channels and Transportersmentioning
confidence: 96%
“…Meanwhile, knockdown of CBS also significantly inhibites the growth of nude mouse tumor xenografts and enhances the inhibition of cisplatin. A team find that in ovarian cancer cell line A2780 cells, GYY4137 induces ER stress under hypoxic conditions, leading to apoptosis in a Ca 2+ -dependent manner [ 96 ]. Moreover, in ovarian cancer cell line A2780, GYY4137 induces intracellular acidification by uncoupling the highly expressed sodium-hydrogen exchanger 1 (NHE1) from sodium-calcium exchanger 1 (NCX1) [ 97 ].…”
Section: The Roles Of H 2 S In Apoptosis In Differ...mentioning
confidence: 99%